Beta 2 microglobulin haemodialysis related amyloidosis: distinctive gross features of gastrointestinal involvement. Issue 10 (October 1997) - Shimizu, M; Manabe, T; Matsumoto, T; Monobe, Y; Hirokawa, M; Moriya, T; Iida, M
Abstract : Two cases of beta 2 microglobulin amyloidosis following long term haemodialysis found during necropsy are reported. The patients were 59 and 65 year old Japanese men, respectively. In both cases, systemic distribution of beta 2 microglobulin amyloid deposits was observed. The gastrointestinal tract including the stomach, small intestine, and colon showed the distinctive gross feature of rippled appearance, which was characterised by serosal wrinkles along the muscle layer arrangement. These areas were confirmed to contain deposits of beta 2 microglobulin in the muscularis propria. Although the outline of the muscle layers was preserved, most muscle fibres, encircled by the amyloid deposits, were atrophic or had disappeared microscopically. In neither case could a definite diagnosis of amyloidosis be made while the patient was alive. Interestingly, the oesophagus presented less involvement compared to the remainder of the gastrointestinal tract. In comparison with the AA or AL type of amyloidosis, beta 2 microglobulin haemodialysis related amyloidosis showed a rippled appearance of the serosal rather than mucosal changes, which may explain the difficulty in diagnosing amyloid deposits using biopsies of the gastrointestinal tract.